Pengaruh Metode Karya Wisata Ke Posyandu Terhadap Peningkatan Kesehatan Anak Tk/Paud Cerdas Desa Tanjung Dolok Kecamatan Marancar” - Pasaribu, Heka Afriannur (Jurnal Kesehatan Ilmiah Aufa Royhan, 2022)
ABSTRACT Health is the most valuable treasure on this earth. Because if we are healthy, we can work doing any activity. But even if we are rich if we are not healthy, it is useless. Health can be obtained by maintaining cleanliness. As the saying goes, cleanliness is the basis of health. Maintaining cleanliness can start from ourselves then the environment around us. Smart kindergarten/PAUD children who were given health education through field trip activities experienced a significant increase in maintaining their health and cleanliness. This can be seen after undergoing counseling, the level of tidiness in dressing and personal hygiene such as cutting nails, brushing teeth has been carried out every day. Kindergarten/Smart preschool children are clean, neat and healthy. Of course this can increase motivation to learn because if the body is healthy then the soul will be strong. Strong to receive lessons and strong to fortify themselves from all kinds of diseases. Keywords: children, health, posyandu, field trip